The use of neural integrity monitor [NIM flextm] tube in patients undergoing posterior fossa surgery: our institutional experience (Indian Journal of Case Reports, 2019)
Neurosurgery for cerebellopontine angle tumour involves handling and dissection of cranial nerves at their origin from the brainstem. Lower cranial nerves or their nuclei may be affected by lesions arising from or extending up to the medulla. Preserving their structural and functional integrity is an important goal during surgical resection. Important functions of vagus nerve include swallowing, speech, respiration and heart rate control and its damage is one of the devastating complications of posterior fossa tumour resection. Electromyographic monitoring for recurrent branch of vagus nerve has been done in thyroid surgeries using a specially designed neural integrity monitor (NIM flexTM) electromyogram (EMG) endotracheal tube containing embedded stimulating electrodes placed at the level of vocal cords. We present our experience with the use of this NIM flexTM EMG endotracheal tube for vagus nerve monitoring in neurosurgery for posterior fossa tumours in four patients. Use of this tube in neurosurgery has been less reported in the Indian literature.